Collaborative optimization of energy conversion and NOx removal in boiler cold-end of coal-fired power plants based on waste heat recovery of flue gas and sensible heat utilization of extraction steam. (15th September 2020) - Han, Yu; Sun, Yingying
Abstract: Based on the close relationship among the feed water heating process, Selective catalytic reduction (SCR) de-NOx and air preheating process, collaborative optimization of energy conversion and NOx removal in the boiler cold-end of coal-fired power plants is proposed in this paper. In the proposed system, recovery of flue gas waste heat and sensible heat efficient utilization of extraction steam provide engineering support for the collaborative optimization concept. The proposed system achieves optimal performance by increasing SCR de-NOx temperature and energy for air preheating. The results reveal that, based on 50% load of a typical 1000 MW coal-fired power plant, the proposed system could increase 5.4 MWe of additional output power with a 0.47% increase of thermal efficiency. The increase of SCR de-NOx temperature brings 6.5% of NOx removal efficiency increase and 28.4 mg/Nm 3 of NOx emission decrease. Besides, the proposed system gains 2.27 million USD of extra annual income. In general, the proposed system achieves great energy savings, NOx removal, and economic performances. Highlights: Collaborative optimization of energy conversion and NOx removal is proposed. Waste heat of flue gas and sensible heat of extraction steam is efficiently used. The system shows great energy-saving, NOx removal, and economic performances. Exergy loss of boiler cold-end in the proposed system is significantly reduced.